Praktek Demokrasi Lokal di Indonesia: Studi Kasus di Kabupaten Lampung Tengah - HAMDI, RIDHO AL (Universitas Muhammadiyah Yogyakarta, 2011)
This study will explain on local democracy experiences in the district level as real evidence to currentIndonesian democracy. It can be shown with several cases of public services in Central Lampung, i.e.the case of corruption on school operational subsidy, the damage of the public street, corruption inmaking ID card, the lacking of water compliance and other problems. This study uses two methods indata gathering, namely in depth interview and participant observation. The result of this study showsthat local bureaucrats not able to maintain and manage public services as a societal basic compliance.Therefore, Central Lampung can be categorized as a weak state. In short, democratically behavior thatcarried out by local elits can not to implement the people prosperity in Indonesia.